Influence of cryopreserved multipotent mesenchymal stromal cells on regulation of immune inflammation in adjuvant arthritis - Vvedenskyi, Dmytro; Volkova, Nataliia; Yukhta, Mariia; Goltsev, Anatoliy (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):305